2015
DOI: 10.1093/mnrasl/slv159
|View full text |Cite
|
Sign up to set email alerts
|

Is the baryon acoustic oscillation peak a cosmological standard ruler?

Abstract: In the standard model of cosmology, the Universe is static in comoving coordinates; expansion occurs homogeneously and is represented by a global scale factor. The baryon acoustic oscillation (BAO) peak location is a statistical tracer that represents, in the standard model, a fixed comoving-length standard ruler. Recent gravitational collapse should modify the metric, rendering the effective scale factor, and thus the BAO standard ruler, spatially inhomogeneous. Using the Sloan Digital Sky Survey, we show to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…The latter type of estimate appears to be convergent with respect to increasing data quality and improved analysis (Blanchard et al 2003;Hunt & Sarkar 2007;Nadathur & Sarkar 2011). As mentioned above, this lower estimate of H bg 0 yields a bg0 = 0.90 ± 0.01, improving the correspondence between the BAO peak shift (shrinkage across superclusters; Roukema et al 2015Roukema et al , 2016) and a bg0 .…”
Section: Astrophysical Age Of Universe Estimates As a Test Of Inhomogsupporting
confidence: 52%
See 1 more Smart Citation
“…The latter type of estimate appears to be convergent with respect to increasing data quality and improved analysis (Blanchard et al 2003;Hunt & Sarkar 2007;Nadathur & Sarkar 2011). As mentioned above, this lower estimate of H bg 0 yields a bg0 = 0.90 ± 0.01, improving the correspondence between the BAO peak shift (shrinkage across superclusters; Roukema et al 2015Roukema et al , 2016) and a bg0 .…”
Section: Astrophysical Age Of Universe Estimates As a Test Of Inhomogsupporting
confidence: 52%
“…pec_expan-bbl which is slightly stronger than the ≈ 10% shrinkage in the BAO peak location detected for Sloan Digital Sky Survey Luminous Red Galaxy pairs whose paths cross superclusters in either the Nadathur & Hotchkiss (2014) or Liivamägi et al (2012) supercluster catalogues (Roukema, Buchert, Ostrowski, & France 2015;Roukema, Buchert, Fujii, & Ostrowski 2016). This suggests that BAO-peak-scale regions crossing superclusters could be considered as a slightly expanded present-day physical realisation of the EdS model extrapolated from early epochs, which we refer to in this paper as our background model.…”
Section: λCdm As An Observational Proxymentioning
confidence: 71%
“…If the environment dependence were genuinely an environment-dependent effect, then it should strengthen as the required overlap between galaxy pairs and superclusters increased. This is indeed the case, as was shown in the recent work presented at the meeting, with the shift increasing up to 10% of the peak location [53]. This presently only qualifies as a qualitative inconsistency with ΛCDM.…”
Section: Recent Observational Resultssupporting
confidence: 53%
“…On a scale up to a little less than 1 h −1 Gpc, Roukema presented recent SDSS DR7 work with Buchert, Fujii and Ostrowski [53] extending previous work [52] that showed that the ≈ 105 h −1 Mpc BAO peak location, normally thought of as a comoving standard ruler, is shrunk by a fraction of 6% across SDSS DR7 superclusters. This is expected from scalar averaging, which can be seen as a generalrelativistically more careful generalisation of the FLRW model [88][89][90], but has not been predicted in the ΛCDM model.…”
Section: Recent Observational Resultsmentioning
confidence: 65%
“…This is indeed the case, as was shown in the recent work presented at the meeting, with the shift increasing up to 10% of the peak location. 53 This presently only qualifies as a qualitative inconsistency with ΛCDM. Future work should confirm whether or not the environmentdependent BAO peak location shift is quantitatively consistent with ΛCDM.…”
mentioning
confidence: 99%